(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Despite the marketing efforts of airlines to differentiate and position their organizations for successful operations in the competitive aviation industry, however, mantaining passengers’ loyalty appears to be a growing concern and challenge to managers in the sector in Nigeria. This study therefore assessed the effect of airlines brand attributes on passengers’ loyalty at Port Harcourt International Airport, Rivers State.This study adopted the cross-sectional survey research design whereby primary data were obtained from 246 passengers of functional airlines at Port Harcourt International Airport through the questionnaire method. The data were analysed using simple percentage, mean score, standard deviation and multiple regression aided by statistical package for social sciences (SPSS). The findings revealed that only safety and baggage handling had a positive and significant effect on passengers’ loyalty to airlines at Port Harcourt International Airport, Rivers State. However, punctuality/reliability of flights did not have a significant effect on passenger loyalty. Based on the findings of the study, it was concluded that airline brand attributes had a varying level of effect on passengers’ loyalty. The study recommended minimization of flight delays and unnecessary flight cancellations as they do not induce passengers’ loyalty.